Реформы Александра II - Чистяков О. И. (Юридическая литература, 1998)
Экземпляры: аб. (1999) / Инвентарный номер: 40952 / Цена: / Сис.шифр: 63.3(2)52 / Авт.знак: Р 45 / ГРНТИ: 03.23.31 / ББК: 63.3(2)52